Mo Yan in Context : Nobel Laureate and Global Storyteller - Huang, Yuhan, 1988-; Duran, Angelica; Project Muse. (West Lafayette, Indiana : Purdue University Press, 2014)
"This is the first English-language study of the Chinese writer's work and influence, featuring essays from scholars in a range of disciplines, from both China and the United States. Its introduction, twelve articles, and epilogue aim to deepen and widen critical discussions of both a specific literary author and the globalization of Chinese literature more generally. The book takes the "root-seeking" movement with which Mo Yan's works are associated as a metaphor for its organizational structure. The four articles of "Part I: Leaves" focus on Mo Yan's works as world literature, exploring the long shadow his works have cast globally. Howard Goldblatt, Mo Yan's English translator, explores the difficulties and rewards of interpreting his work, while subsequent articles cover issues such as censorship and the "performativity" associated with being a global author. "Part II: Trunk" explores the nativist core of Mo Yan's works. Through careful comparative treatment of related historical events, the five articles in this section show how specific literary works intermingle with China's national and international politics, its mid-twentieth-century visual culture, and its rich religious and literary conventions, including humor. The three articles in "Part III: Roots" delve into the theoretical and practical extensions of Mo Yan's works, uncovering the vibrant critical and cultural systems that ground Eastern and Western literatures and cultures. Mo Yan in Context concludes with an epilogue by sociologist Fenggang Yang, offering a personal and globally aware reflection on the recognition Mo Yan's works have received at this historical juncture"--
Introduction to Mo Yan in context : Nobel Laureate and Global Storyteller / Angelica Duran and Yuhan Huang -- A mutually rewarding yet uneasy and sometimes fragile relationship between author and translator / Howard Goldblatt -- The Censorship of Mo Yans The Garlic Ballads / Thomas Chen -- Representations of China and Japan in Mo Yans, Hayashis and Naruse's texts / Noriko J. Horiguchi -- Abortion in Faulkner's The Wild Palms and Mo Yan's Frog / Lanlan Du -- Rural Chineseness Mo Yan's Work and World Literature / Chengzhou He -- The Realpolitik of Mo Yans Fiction / Sabina Knight -- Mo Yans Life and Death Are Wearing Me Out in a cultural and visual context / Yuhan Huang -- Mo Yan's The Garlic Ballads and Lide and Death Are Wearing Me Out in the Context of Religious and Chinese Literary Conventions / Chi-ying Alice Wang -- Religious Elements in Mo Yans and Yan Lianke's Works / Jinghui Wang -- Mo Yans work and the politics of literary humor / Alexa Huang and Angelica Duran -- Cosmopolitanism and the internationalization of Chinese literature / Ning Wang -- Variation study in Western and Chinese comparative literature / Shunqing Cao and Miaomiao Wang -- Soul Searching in Contemporary Chinese Literature and Society / Fenggang Yang.
In English.
Description based on print version record.
Keywords: Mo, Yan -- 1956-; Mo, Yan, -- 1955-; Mo, Yan, -- 1955- -- Criticism and interpretation; Mo, Yan, -- 1955- -- Criticism and interpretation; Literaturkritik; Kontextanalyse; Nobelpreisträger; Schriftsteller; LITERARY CRITICISM -- Asian -- General; LITERARY CRITICISM -- Asian -- Chinese; LITERARY CRITICISM -- Asian -- General; Criticism, interpretation, etc; Electronic books